Preparatory routines for emotional regulation in performance enhancement - Orbach, Iris; Blumenstein, Boris (Frontiers in Psychology, 2022)
Preparatory routines (PR) are a necessary tool for achieving optimal emotional states and effective performance, especially in self-paced motor skills. Numerous studies in the area of applied sport psychology have found a positive effect of PR on blocking out distractions and regulating performance thoughts, actions, and emotions. PR contain behavioral and mental components that can be applied in different time periods before and after the event itself: pre-competitive activity routines (PCA-R), pre-performance routines (PP-R), and post-performance activity routines (PPA-R). The aim of this manuscript is to present an effective way to practice psychological techniques and their combinations as part of the PR. The periodization principle and the Learning-Modification-Application (LMA) model with biofeedback training can provide a conceptual framework and means of application for performance enhancement. It will allow the transfer of psychological skills from lab to field and the integration of PR into the athlete's preparations for peak performance.